LEVEL OF KNOWLEDGE AND ATTITUDE TOWARDS ANTIBIOTIC USE IN THE COMMUNITY OF JORONG SIMPANG EMPAT NAGARI LINGKUANG AUA DISTRICT OF WEST PASAMAN - Rida Rosa; Aprilianda Aprilianda; Isna Desvera; ully chairunisa (Indonesian Journal of Pharmaceutical Research, 2025)
Abstract: Antibiotics are used to prevent and treat infections, their use must be in accordance with a doctor's prescription. The use of antibiotics that are not in accordance with a doctor's prescription will have negative impacts such as resistance to one or more antibiotics, increased side effects of drugs and increased costs in antibiotic treatment. This study aims to determine the level of antibiotic knowledge and attitudes towards the correct use of antibiotics in the community of Jorong Simpang Empat Nagari Lingkuang Aua Kabupaten PasamanBarat. This study is a descriptive study that is observational with a cross-sectional approach to 100 respondents who meet the inclusion criteria. The results of the study obtained were the level of antibiotic knowledge in the community of Jorong Simpang Empat which was included in the good category 53%, the sufficient category 16%, the less category 31% and for the attitude of antibiotic use in the community of Jorong Simpang Empat the good category 59%, the sufficient category 38%, the less category 3% And there is a significant relationship between the level of knowledge and attitudes towards the use of antibiotics with a significance value of 0.001Keywords: level of knowledge, attitudes, antibiotics